Brucella infection induces chromatin restructuring in host cells to activate immune responses - Xie, Dejian; Xu, Heling; Su, Changwei; Lu, Jingjing; Shen, Wenlong; Li, Ping; Ye, Bingyu; Hou, Jiabao; Deng, Junwei; Zhang, Yan; Li, Shanhu; Zhao, Zhihu (Frontiers in Immunology, 2025)
BackgroundBrucella spp., facultative intracellular pathogens that cause brucellosis, drive pathogenesis by invading host cells and establishing intracellular persistence. While their molecular mechanisms are well-characterized, how Brucella induces chromatin restructuring in host cells remains poorly understood, representing a critical gap in host-pathogen interaction research.MethodsUsing an established in vitro infection model of Brucella-infected RAW264.7 murine macrophages, we integrated Hi-C, ATAC-seq, and RNA-seq to generate multi-omics datasets. Multidimensional comparative genomics approaches were employed to systematically map infection-induced changes in host chromatin architecture and functional genomic organization.ResultsOur findings unveiled substantial alterations in the host chromatin architecture, characterized by a reduction in B-B compartment regions interactions, an increase in A-B compartment interactions, and diminished long-range chromatin contacts. Crucially, Brucella reshaped chromatin compartmentalization, activating interferon-stimulated genes (ISGs) in regions transitioning from compartment B to A. Enhanced sub-TADs interactions within ISG clusters further facilitated their coordinated expression. Additionally, infection remodeled chromatin loop structures, strengthening interactions linked to immune-related gene activation.ConclusionThese results demonstrate that host cells undergo substantial chromatin remodeling during acute Brucella infection as a defense mechanism against pathogen invasion. Our findings provide critical insights into host-pathogen interactions and suggest potential epigenetic targets for managing brucellosis.